2008
DOI: 10.1080/14622200802163092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine on affect are moderated by stressor proximity and frequency, positive alternatives, and smoker status

Abstract: The Situation x Trait Adaptive Response (STAR) model hypothesizes that nicotine reduces negative and enhances positive affect to a greater degree in situations involving internally driven attention, as when stressor stimuli are distal (past or future), thereby allowing nicotine-primed biasing of attentional processing away from negative and toward positive stimuli. To test this hypothesis, the effects of nicotine were assessed in 64 smokers and 64 never-smokers, half of whom viewed emotionally negative picture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 27 publications
2
28
1
Order By: Relevance
“…This finding in A2 individuals is consistent with other findings and theory (Gilbert, 1995; Gilbert et al, 2008a) suggesting that nicotine attenuates processing of negative affect when the negative stimulus is more temporally distal and less proximal. For example, Gilbert et al (2008a) found greater reduction in negative affect by nicotine during the distal periods (shortly after stressors), than during actual stressor exposure, as well as reduced attentional bias (eye-gaze) toward negative pictures, relative to positive pictures, during the later but not earlier portions of picture presentations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding in A2 individuals is consistent with other findings and theory (Gilbert, 1995; Gilbert et al, 2008a) suggesting that nicotine attenuates processing of negative affect when the negative stimulus is more temporally distal and less proximal. For example, Gilbert et al (2008a) found greater reduction in negative affect by nicotine during the distal periods (shortly after stressors), than during actual stressor exposure, as well as reduced attentional bias (eye-gaze) toward negative pictures, relative to positive pictures, during the later but not earlier portions of picture presentations.…”
Section: Discussionsupporting
confidence: 92%
“…Pictures were similar in terms of complexity, color, saturation, and brightness and were selected from the International Affective Picture System (Lang et al, 1995) and our laboratory (Gilbert et al, 2008a). The mean valence scores on the Lang et al 9-point scale for these pictures were (standard deviations in parentheses): negative 2.86 (.98), positive 6.93 (.99) and neutral 4.90 (.73), where “1” = extremely negative through “9” = “extremely positive”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expectations that smoking confers rewards (e.g., enjoyable, something to do when bored, stay thin) increases the likellihood that depressed adolescents will choose to smoke. As nicotine can ameliorate the affective and reward processing deficits associated with depression (Barr et al, 2008; Gilbert et al, 2008; Kenny and Markou, 2006; Spring et al, 2008; Warburton and Mancuso, 1998), and impact neurocognitive processes that are typicaaly diminished in depression (Evans and Drobes, 2009; Gilbert et al, 2008; Heishman et al, 2010), these adolescents may indeed learn that smoking is rewarding. Thus, their smoking experience may then serve to validate their expectations.…”
Section: Discussionmentioning
confidence: 99%
“…The 20-item PANAS (Watson et al 1988) was scored to produce positive affect and negative affect scales which are internally reliable, and have been extensively validated (Watson et al 1999). Six items from the FSQ (irritable, attentive, jittery, nauseous, sick, and dizzy Gilbert et al 2008) were administered to assess commonly reported aversive effects of nicotine.…”
Section: Methodsmentioning
confidence: 99%